Second Five Year Plan Progress Report for 1957-58 Himachal Pradesh Administration - Planning Commission (Planning Commission, 1957)
As in other parts of the country, the Second Five Year Plan of Himachal Pradesh is in essence a continuation and, in accordance with the growing needs of the people, feasible expansion or intensification of the process of development initiated during the First Plan. the total outlay of Rs. 1,472.53 lakhs on the Second Plan of the Pradesh is more than twice on the First. In terms of financial allocation, development of roads and road-transport, which is an essential pre-requisite for the execution of development projects in a difficult hilly terrain like Himachal Pradesh, continues to receive priority. Moreover, the Second Plan is characterised by the inclusion of various schemes relating to. (i) welfare of backward classes, (ii) social welfare and (iii) labour and labour welfare.
Himachal Pradesh Administration